Current research status and trends of potassium-competitive acid blockers in the treatment of acid-related diseases: a bibliometric analysis - Zhu, Baoqiang; Chen, Long; Tao, Xue; Zheng, Hong; Li, Xia; Wu, Qingfang; Long, Enwu; Lin, Haixia (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the current research status and trends of potassium-competitive acid blockers (P-CABs) in the treatment of acid related diseases (ARDs) using bibliometric analysis.Materials and methodsWe collected publications related to P-CAB in the treatment of acid-related diseases in the Web of Science (WOS) Core Collection from the establishment of the database to 30 June 2024. We evaluated the publication volume and citation status over the years using the WOS platform, and visualized the authors, countries, institutions, keywords, and citations of the publications using CiteSpace and VOSviewer.ResultsThis study included a total of 455 articles. The number of publications and citations related to research has been increasing year by year. The results show that the scholars with the highest number of publications mainly come from South Korea and Japan. Scholars such as Geun Seog Song, Bongtae Kim, and Nobuhiro Inatomi produced many works in related fields. The most popular drug in this field was vonoprazan, and research on this drug mainly focused on the effectiveness and safety evaluation of ARDs such as Helicobacter pylori infection, gastroesophageal reflux disease, peptic ulcers, etc. Researchers were concerned about the evaluation of treatment regimens and efficacy comparison between P-CABs and traditional proton pump inhibitors (PPIs) in the treatment of ARDs. At the same time, researchers are also closely monitoring the potential adverse reactions and long-term adverse outcomes of clinical application of P-CABs for ARDs.ConclusionThe clinical application of P-CABs, represented by vonoprazan, in ARDs is receiving widespread attention from researchers. The exploration of the application of this type of drug in ARDs is constantly expanding, and it is a research field with great clinical value and research potential.